The Effect of Beet Juice Intake on Increasing Hemoglobin Levels in Adolescent Girls with Anemia: A Literature Review - Handayani, Oktavia; Widhi Astuti, KH Endah; Puspita Sari, Lutfiana (Jurnal Kebidanan dan Kesehatan Tradisional, 2024)
Background: Anemia in adolescent girls is a health problem that is still commonly found and has an impact on decreased learning concentration, productivity, and reproductive health. One non-pharmacological alternative that can help increase hemoglobin levels is the consumption of beet juice, which contains iron, folate, and vitamin C. This study aims to determine the effectiveness of beetroot juice in increasing hemoglobin levels in adolescent girls with anemia.  Methods: This study used a literature review design by searching articles from the Google Scholar and PubMed databases. The search strategy was conducted using the keywords "beetroot effect," "blood hemoglobin," "beetroot benefit," and "anemia." The articles analyzed were selected based on inclusion and exclusion criteria relevant to the topic, resulting in 10 eligible journals. The data were analyzed descriptively by examining the study design, sample size, intervention, and results of hemoglobin level improvement.  Results: The review showed that all ten journals reported a significant increase in hemoglobin levels after regular consumption of beetroot juice in adolescent girls with anemia. The nutrients in beetroot play a role in red blood cell formation and increasing blood oxygen capacity.  Conclusion: Beet juice is effective in increasing hemoglobin levels in adolescent girls with anemia. Nutrition education programs for adolescents should recommend beet juice consumption as a natural alternative to increase hemoglobin levels.